2011
DOI: 10.1542/peds.2009-3068
|View full text |Cite
|
Sign up to set email alerts
|

Coprescription of Antibiotics and Asthma Drugs in Children

Abstract: WHAT THIS STUDY ADDS:In this study, antibiotic use was found to be 1.9 times more frequent in children who were treated with asthma drugs than those who were not. Among children who received an asthma drug, 35.6% were dispensed an antibiotic on the same day. abstract BACKGROUND: In children, antibiotics as well as asthma drugs are frequently prescribed. We investigated the effects of the codispensing of antibiotics and asthma drugs to children. METHODS:Using a health insurance database, we examined dispensing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
35
1
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(40 citation statements)
references
References 14 publications
3
35
1
1
Order By: Relevance
“…The observed differences in the prevalence and average number of anti-infective prescriptions between different sex and age categories in both cohorts are in line with the results of other studies (20)(21)(22). In our study, the highest prevalence for antiinfective prescriptions was observed for boys who developed type 1 diabetes at the age of 0 to 4 years.…”
Section: Discussionsupporting
confidence: 91%
“…The observed differences in the prevalence and average number of anti-infective prescriptions between different sex and age categories in both cohorts are in line with the results of other studies (20)(21)(22). In our study, the highest prevalence for antiinfective prescriptions was observed for boys who developed type 1 diabetes at the age of 0 to 4 years.…”
Section: Discussionsupporting
confidence: 91%
“…De Boeck et al used a health insurance database that encompassed the records from 892 841 Belgian children seen in 1 year to examine antibiotic-prescribing practices. They reported that 36.62% of the children without an asthma medication received an antibiotic while 73.50% children with an asthma medication did so [35]. Stallworth et al [36] reported that pediatric asthmatic patients received significantly more antibiotic prescriptions than non-asthmatics for conditions caused by bacteria as well as for conditions more likely to be viral in origin.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, Jedrychowski et al [38] conducted a birth cohort with 310 Polish children and found that the overall use of antibiotics during early childhood was insignificantly associated with asthma (OR ¼ 1.65, 95% CI: 0.93-2.93), although the crude OR was significant (OR ¼ 2.14, 95% CI: 1.37-3.34). There have been several additional reports of asthma associated with clinical antibiotic exposures in the literature [30][31][32][33][34][35]. One such study found an extremely elevated prevalence of asthma in children with high exposures to clinical antibiotics in the first three years of life, especially in those with nonatopic asthma [30].…”
Section: Discussionmentioning
confidence: 99%
“…6,7 De Boeck et al 6 used a health insurance database that encompassed the records of 892 841 Belgian children seen in 1 year to examine antibiotic-prescribing practices. During this period, an antibiotic was dispensed to 44.21% of the children covered by this insurance provider, and an asthma drug (␤-adrenergic agents, inhaled corticosteroid, ipratropium, and/or leukotriene receptor antagonist) was dispensed to 16.04%.…”
mentioning
confidence: 99%
“…De Boeck et al 6 had access to data from a health care insurer that covers 44% of the population of Belgium, where medical insurance coverage is mandatory. Although neither study directly assessed the complaints and findings that led to prescription of either antibiotic or bronchodilator therapy, the results suggest that Belgian and American physicians prescribe antibiotics for patients perceived to have a diagnosis of asthma or bronchospasm at a previously unsuspected level: as often as 1 in 6 visits for American children, which accounts for 1 million or more dubious prescriptions per year.…”
mentioning
confidence: 99%